Perancangan Sistem Informasi Rapor Digital Siswa Berbasis Mobile Menerapkan RAD - Muhamad Alda; Nabilah Safitri; Dwi Alisya; Ahnaf Chaisar Akbar; Dimas Arya Wardana (TIN: Terapan Informatika Nusantara, 2026)
The development of information and communication technology has encouraged educational institutions to adopt digital systems for managing academic data, including the preparation and distribution of student report cards. This study aims to design and develop a mobile-based Digital Report application using the Kodular platform as a solution to the inefficiency and errors of manual systems. The development method used is Rapid Application Development (RAD), focusing on quick iterations through stages of requirement analysis, interface design, and functional testing. Data were collected through literature study, observation, and interviews with schools to ensure that the application features met user needs. The results show that the application provides login, dashboard, student data input, score management, and real-time report access. Implementation of the Kodular no-code platform in the development of a mobile-based digital report card system that is easy to implement in the school environment, as well as providing an efficient and adaptive academic system development model for schools with limited technical resources. Kodular proved effective in speeding up the development process without complex coding, supporting school digitalization, and improving transparency and efficiency in managing academic data.